Commencement 2007 (Institutional Knowledge at Singapore Management University, 2007)
Salutatorian Li Xiangrun addressing the crowd at Singapore Management University's fourth commencement ceremony. He earned a bachelor of economics degree summa cum laude, The event was held at Suntec City Convention Centre on 14 July 2007.